2002
DOI: 10.1073/pnas.232186099
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the 22q11 locus and susceptibility to schizophrenia

Abstract: An increased prevalence of microdeletions at the 22q11 locus has been reported in samples of patients with schizophrenia. 22q11 microdeletions represent the highest known genetic risk factor for the development of schizophrenia, second only to that of the monozygotic cotwin of an affected individual or the offspring of two schizophrenic parents. It is therefore clear that a schizophrenia susceptibility locus maps to chromosome 22q11. In light of evidence for suggestive linkage for schizophrenia in this region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
141
2
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(163 citation statements)
references
References 37 publications
11
141
2
9
Order By: Relevance
“…12,13,19,20,[60][61][62] They are especially interesting as the same regions may encompass susceptibility genes for schizophrenia. [63][64][65][66][67][68][69][70] Park et al 71 made similar conclusions in a study of psychotic BD in which most areas of linkage overlapped with those reported in previous investigations of schizophrenia.…”
Section: Psychotic Symptoms In Bdsupporting
confidence: 71%
“…12,13,19,20,[60][61][62] They are especially interesting as the same regions may encompass susceptibility genes for schizophrenia. [63][64][65][66][67][68][69][70] Park et al 71 made similar conclusions in a study of psychotic BD in which most areas of linkage overlapped with those reported in previous investigations of schizophrenia.…”
Section: Psychotic Symptoms In Bdsupporting
confidence: 71%
“…To identify potential functional polymorphisms in these four genes that could contribute to schizophrenia susceptibility, as well as polymorphisms that could be used for association studies, we determined the sequence of coding and noncoding exons, splice donor and acceptor sites, and some intronic and promoter regions of these genes in genomic DNA isolated from 12 independent schizophrenia patients (U.S. schizophrenia sample) (18,19). The obtained sequences were compared with the human draft sequence to identify polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…Insertion͞deletion polymorphisms were typed by PCR of genomic DNA from individual subjects and identified by altered fragment size as assessed by agarose gel electrophoresis. SNPs were typed either by PCR-restriction fragment length polymorphism genotyping or by fluorescence polarization templatedirected dye-terminator incorporation genotyping as described (18,19). See supporting information for genotyping primer sequences.…”
mentioning
confidence: 99%
“…Our data suggests additional candidates (particularly Ranbp1 and Cdc45l) as potential contributors to altered cortical development in 22q11DS. RANBP1 polymorphisms have been associated with schizophrenia vulnerability in non-22q11 deleted individuals (45) and restricted CDC45L, as well as UFD1L, deletion has been associated with 22q11DS clinical features including heart, craniofacial, and thymic anomalies (42). The cell-cycle functions of both Ranbp1 and Cdc45l, their diminished expression in LgDel VZ/SVZ, and parallel diminished expression of CyclinD1 and E2f2, major regulators of the G1/S check point, indicate that local activity of 22q11 genes may inf luence cortical cell-cycle dynamics.…”
Section: Discussionmentioning
confidence: 99%